Cosmoball [videorecording (DVD)] - Agalakova, Viktoriya; Ivanova, Svetlana, 1985-; Efremov, Mikhail, 1963- (Universal Pictures Home Entertainment, 2021)
Life on earth is desolate after a brutal intergalactic war, brightened only by the dangerous, high-flying sport Cosmoball, but no one knows that at each match, four gifted humans are fighting furiously to ensure the survival of humankind.